Adding Azathioprine to Remission‐Induction Glucocorticoids for Eosinophilic Granulomatosis With Polyangiitis (Churg‐Strauss), Microscopic Polyangiitis, or Polyarteritis Nodosa Without Poor Prognosis Factors: A Randomized, Controlled Trial. Issue 11 (15th October 2017) - Puéchal, Xavier; Pagnoux, Christian; Baron, Gabriel; Quémeneur, Thomas; Néel, Antoine; Agard, Christian; Lifermann, François; Liozon, Eric; Ruivard, Marc; Godmer, Pascal; Limal, Nicolas; Mékinian, Arsène; et al.
Abstract : Objective: In most patients with nonsevere systemic necrotizing vasculitides (SNVs), remission is achieved with glucocorticoids alone, but one‐third experience a relapse within 2 years. This study was undertaken to determine whether the addition of azathioprine (AZA) to glucocorticoids could achieve a higher sustained remission rate of newly diagnosed nonsevere eosinophilic granulomatosis with polyangiitis (Churg‐Strauss) (EGPA), microscopic polyangiitis (MPA), or polyarteritis nodosa (PAN). Methods: All patients included in this double‐blind trial received glucocorticoids, gradually tapered over 12 months, and were randomized to receive AZA or placebo for 12 months, with stratification according to SNV (EGPA or MPA/PAN). The primary end point was the combined rate of remission induction failures and minor or major relapses at month 24. Results: Ninety‐five patients (51 with EGPA, 25 with MPA, and 19 with PAN) met the inclusion criteria, were randomized, and received at least 1 dose of AZA (n = 46) or placebo (n = 49). At month 24, 47.8% of the patients receiving AZA versus 49% of the patients receiving placebo had remission induction failures or relapses ( P = 0.86). Secondary end points were comparable between the AZA and placebo arms. These included initial remission rate (95.7% versus 87.8%), total relapse rate (44.2% versus 40.5%), and glucocorticoid use. Two patients in the placebo arm died; 22 patients in the AZA arm (47.8%) and 23 patients in the placebo arm (46.9%) experienced ≥1 severe adverse event. For EGPA patients, the primary end point (48% in the AZA arm versus 46.2% in the placebo arm) and the percent of patients who experienced asthma/rhinosinusitis exacerbations (24% in the AZA arm versus 19.2% in the placebo arm) were comparable between treatment arms. Conclusion: Addition of AZA to glucocorticoids for the induction of remission of nonsevere SNVs does not improve remission rates, lower relapse risk, spare steroids, or diminish the EGPA asthma/rhinosinusitis exacerbation rate.